Studi Penokohan dalam Novel Moga Bunda Disayang Allah Karya Tere Liye - Resti Andini; Liza Septa Wilyanti; Nurfadilah (Pusat riset dan Inovasi Nasional, 2026)
This research is motivated by the importance of studying characterization in novels as a means of understanding human values ​​and character education relevant to social reality. Tere Liye's novel